Exploring an Entrepreneurial Prospective of English Language to Promote Muaro Jambi Temple - Nyimas Triyana Safitri; Hidayati; Dedy Kurniawan; Friscilla Wulan Tersta (Universitas Pendidikan Ganesha, 2023)
Many of our cultural assets have been lost as a result of not being adequately protected. One way to prevent this situation is to carry out effective conservation at the educational level. This study aims to develop learning model to be implemented to promote a tourist destination of Candi muaro jambi as one of the cultural heritages. Research and Development with ADDIE model is used in this study. ADDIE model consist of analysis, design, development, implementation, and evaluation. This research involved the local communities where this program was implemented, five students and five English Lecturers of the English Study Program. There are three main research instruments, the fifth semester course documents of the English Study Program, field survey and interview. Data were analysed using qualitative techniques. The result reveals three prospective schemes of English language needed by local people to endorse Candi Muaro. They are daily talk of English language training for local communities, technological utilization for tourist publication and promotion, and English tour guiding Instruction. It is expected these outcomes can accelerate the development of Candi Muaro Jambi to be well-promoted and it is further recommended to explore more about other outlooks of Candi Muaro Jambi to be famous to all over the countries around the world.